Chasing elusive expressive writing effects: emotion-acceptance instructions and writer engagement improve outcomes - Rude, Stephanie S.; Lantrip, Crystal; Aguirre, Vanessa A.; Schraegle, William A. (Frontiers in Psychology, 2023)
Introduction: Pennebaker’s expressive writing (EW) paradigm in which participants are encouraged to explore their “deepest thoughts and feelings” about a difficult experience in several short writing sessions has yielded impressive mental health outcomes and holds great promise as a cost-effective intervention. Yet results have been difficult to replicate and it is unclear what conditions are necessary for observing the effect. Our aim was to discover reasons for the variability in EW outcomes. We explored the impact of augmenting writing instructions to encourage acceptance of emotional experience, which we thought would encourage engagement with writing; and we examined essay length, an index of writer engagement, as a possible moderator of writing outcomes. Methods: We compared traditional expressive writing (tEW), conducted according to Pennebaker’s paradigm in which participants write about a self-chosen emotional experience for 15 minutes at a time on each of three closely spaced days, with an acceptance-enhanced version (AEEW), identical except that it supplemented traditional instructions with encouragement of an accepting approach to emotional experience, and with a control condition which asked participants to write about their use of time on particular days. Self-reported depression was the outcome measure. Results: Essay length (a proxy for writer engagement) moderated effects of writing at posttest two weeks later: Condition differences were found only for participants who wrote longer essays: For these participants the AEEW condition outperformed both control and tEW; and tEW did not differ significantly from control. Conclusion: Findings suggest that degree of engagement in the writing process may partially explain the puzzle of variable outcomes in the EW literature. Results also provide practical guidance: Those who are motivated to engage deeply in the writing process are most likely to benefit; and encouraging writers to accept and to openly explore emotional experience is expected to enhance benefits.